MATRIX METALLOPROTEINASES AND THEIR FUNCTION IN MYOCARDIUM - Kukacka, Jiri; Prusa, Richard; Kotaska, Karel; Pelouch, Vaclav (Biomedical papers, 2005)
A significant number of myocardial diseases are accompanied by increased synthesis and degradation of the extracellular matrix (ECM) as well as by changed maturation and incorporation of ECM components. Important groups of enzymes responsible for both normal and pathological processes in ECM remodeling are matrix metaloproteinases (MMPs). These enzymes share a relatively conserved structure with a number of identifiable modules linked to their specific functions. The most important function of MMPs is the ability to cleave various ECM components; including such rigid molecules as fibrillar collagen molecules. The amount and activity of MMPs in cardiac tissue are regulated by a range of activating and inhibiting processes. Although MMPs play multifarious roles in many myocardial diseases, here we have focused on their function in ischemic cardiac tissue, dilated cardiomyopathy and hypertrophied cardiac tissue. The inhibition of MMPs by means of synthetic inhibitors seems to be a promising strategy in cardiac disease treatment. Their effects on diseased cardiac tissue have been successfully tested in several experimental studies.
Keywords: Extracellular matrix/Matrix metalloproteinases (MMPs)/Myocardium/Remodeling/MMP inhibitors